Manuscripts from our global past - Noor, Farish A. (Biblioasia)
The 'Tales of the Malay World: Manuscripts and Early books' exhibition in Singapore's National Library showcases how the Southeast Asian region has long been globalised and remind us that the region has been a centre of learning and writing.